Emotional intelligence and the academic and clinical performances of clinical clerks - Chua, Mitzi Marie M.; Nemuel Fajutagana S., MD MHPED (Manila The National Teacher Training Center for the Health Professions, 2021)
Emotional intelligence (EI) is related to better physician well-being, improved patient care and enhanced doctor-patient relationship. EI-related competencies should therefore be better developed in medical students who will be future doctors. This study generated the EI profile of clerks in a Philippine medical school. It aimed to (1) characterize the clerks’ demographic profile as to age, sex, religious affiliation, pre-medicine college degree and history of academic failure; (2) describe their profile as to academic achievement (GWA), clinical performance and ability EI, measured by Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT); and (3) determine association between EI and academic achievement, clinical performance, and demographic factors. This was a prospective correlational study in one medical school in Central Philippines. MSCEIT was administered online. Descriptive data are presented with frequencies and mean scores. Pearson’s correlation coefficient and chi- square tests were done for EI association analyses. Among 127 clerks, 65% (n=83) were females and the mean age was 25.62 years. Medical Technology was the most common preparatory course (54%). Majority (67%) were Catholics. Only 13 students had prior academic failures. Mean academic GWA was 79.06% (73.53-87.94%), compared to mean overall clinical performance (88.17, 83.61-92.33%) and subcategory grade on professionalism, attitude and ethics (87.35, 83.25-91.80%]). Mean MSCEIT EIQ was low average at 95.52 (60.14-128.21). Strategic EIQ (97.95) was higher than experiential EIQ (95.43). Understanding Emotions had the highest branch score (101.61); Managing Emotions was lowest (94.30). EI had negligible correlations with: (1) academic GWA [r(127) = -.044,p = .622], (2) clinical performance [r(127) = -.059,p = .513],, and (3) subcategory on ethics, professionalism, and attitude [r(127) = -.043,p = .634]. EI was not significantly associated with demographic factors of sex (X2(3,N = 127) = 3.01, p = .39), age [X2(3,N = 127) = 2.10, p = .55], pre-medicine course [X2(3,N = 118) = 3.79, p = .29], religion [X2(3,N = 108) = 1.13, p = . 77], and prior academic failures [X2(3,N = 127) = 1.97, p = .58]. In conclusion, the clerks’ mean overall MSCEIT EIQ score was low average. EI was not significantly associated with academic achievement, clinical performance and demographic variables. The researcher recommends studying EI changes through time, trying trait EI tool, and assessing EI in relation to mental health while learning amidst the pandemic.
Thesis (Master in Health Professions Education)
Panel members: Nemuel Fajutagana, MD, MHPEd, Chair/Adviser. Jusie Lydia J. Siega-Sur, MHPEd, Reader/Critic. Members: Erlyn A. Sana, PhD; Corazon T. Meneses, MD; Manuel Emerson Donaldo, MD.
Keywords: Emotional Intelligence; Academic achievement; Clinical performance; Clinical clerks